Virus–host interplay in hepatitis B virus infection and epigenetic treatment strategies. (19th May 2017) - Hensel, Kai O.; Rendon, Julio C.; Navas, Maria‐Cristina; Rots, Marianne G.; Postberg, Jan
Abstract : Worldwide, chronic hepatitis B virus (HBV) infection is a major health problem and no cure exists. Importantly, hepatocyte intrusion by HBV particles results in a complex deregulation of both viral and host cellular genetic and epigenetic processes. Among the attempts to develop novel therapeutic approaches against HBV infection, several options targeting the epigenomic regulation of HBV replication are gaining attention. These include the experimental treatment with 'epidrugs'. Moreover, as a targeted approach, the principle of 'epigenetic editing' recently is being exploited to control viral replication. Silencing of HBV by specific rewriting of epigenetic marks might diminish viral replication, viremia, and infectivity, eventually controlling the disease and its complications. Additionally, epigenetic editing can be used as an experimental tool to increase our limited understanding regarding the role of epigenetic modifications in viral infections. Aiming for permanent epigenetic reprogramming of the viral genome without unspecific side effects, this breakthrough may pave the roads for an ambitious technological pursuit: to start designing a curative approach utilizing manipulative molecular therapies for viral infections in vivo . Abstract : Schematic outline of the virus–host interplay in HBV infection and the dynamic epigenome. HBV infection bears significant impact on essential gene transcription processes through various alterations of both viral and host epigenetic signatures with. Several of these can be experimentally targeted using epidrugs or epigenetic editing (indicated by crosshairs).